2001
DOI: 10.1128/aac.45.4.1094-1098.2001
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Prospective Controlled Trial of Recombinant Granulocyte Colony-Stimulating Factor as Adjunctive Therapy for Limb-Threatening Diabetic Foot Infection

Abstract: limb-threatening foot infection were consecutively enrolled in a prospective, randomized, controlled clinical study aimed at assessing the safety and efficacy of recombinant human granulocyte colony-stimulating factor (G-CSF) (lenograstim) as an adjunctive therapy for the standard treatment of diabetic foot infection. Forty patients, all of whom displayed evidence of osteomyelitis and long-standing ulcer infection, were randomized 1:1 to receive either conventional treatment (i.e., antimicrobial therapy plus l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
2
8

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(77 citation statements)
references
References 19 publications
1
65
2
8
Order By: Relevance
“…Multiple studies of G-CSF in nonneutropenic animal models have demonstrated improvements in outcome (172,276,312,322,433). In human studies, improvements in laboratory markers are seen following G-CSF use (186,242,360), and patients with diabetic foot infection may benefit from the use of G-CSF (134,175). However, large multicenter clinical trials have failed to demonstrate benefits in pneumonia and severe sepsis, possibly due to late administration of G-CSF in the course of the illness (85,310,311,361).…”
Section: Role Of Host Immune Responsesmentioning
confidence: 99%
“…Multiple studies of G-CSF in nonneutropenic animal models have demonstrated improvements in outcome (172,276,312,322,433). In human studies, improvements in laboratory markers are seen following G-CSF use (186,242,360), and patients with diabetic foot infection may benefit from the use of G-CSF (134,175). However, large multicenter clinical trials have failed to demonstrate benefits in pneumonia and severe sepsis, possibly due to late administration of G-CSF in the course of the illness (85,310,311,361).…”
Section: Role Of Host Immune Responsesmentioning
confidence: 99%
“…However, some investigations reported that treatment by G-CSF improves symptoms but not signs of myocardial ischemia in patients with severe ischemic heart disease (25). The adjunctive treatment with G-CSF for 3 weeks was well tolerated but could not significantly affect the clinical and biological parameters of the healing process in diabetic patients with severe limbthreatening infection (26). We have also treated two patients with diabetic CLI G-CSF alone and have not observed obvious improvement of the main clinical manifestations at 12 weeks (data not shown).…”
Section: Huang and Associatesmentioning
confidence: 99%
“…Two adjunctive modalities do deserve brief comments. First, granulocyte colony-stimulating factors (G-CSFs) have now been investigated in 5 randomized trials involving diabetic foot infections [223][224][225][226][227]. A preliminary meta-analysis of these trials suggests that G-CSF does not accelerate resolution of infection but may significantly reduce the need for operative procedures (B-I) [228].…”
Section: Treatment Of Infectionmentioning
confidence: 99%